Role of female sex hormones, estradiol and progesterone, in mast cell behavior - Zierau, Oliver; Zenclussen, Ana C.; Jensen, Federico (Frontiers in Immunology, 2012)
Female sex hormones have long been suspected to have an effect on mast cell (MC) behaviour. This assumption is based on the expression of hormone receptors in MCs as well as on the fact that many MC-related pathophysiological alterations have a different prevalence in females than in males. Further, serum IgE levels are much higher in allergic female mice compared to male mice. Ovariectomized rats developed less airway inflammation compared to sham controls. Following estrogen replacement ovariectomized rats re-established airway inflammation levels’ found in intact females. In humans, a much higher asthma prevalence was found in women at reproductive age as compared to men. Serum levels of estradiol and progesterone have been directly correlated with the clinical and functional features of asthma. Around 30 to 40% of women who have asthma experienced worsening of their symptoms during the perimenstrual phase, the so-called perimenstrual asthma. Postmenopausal women receiving hormone replacement therapy have an increased risk of new onset of asthma. Beside, estrus cycle dependent changes on female sex hormones are related to changes on MC number in mouse uterine tissue and estradiol and progesterone were shown to induce uterine MC maturation and degranulation. We will discuss here the currently available information concerning the role of these female sex hormones on MC behavior.